Pemberantasan Stunting dan Penatalaksanaan Permasalahan Kesehatan Menuju Masyarakat Sehat di Desa Tanjung Putra - Hadriyati, Armini; Andini, Thalia Rizky; Noviyanti, Viona; Putri, Suci Isnaini; Firira, Camila Putri; Irmadayanti, Desma Silvia; Hutagalung, Syafitri; Alhadi, Muhammad Arif (Universitas Baiturrahim, 2024)
The problems of stunting in Tanjung Putra Village include the high incidence of stunting in toddlers, lack of understanding of the importance of nutrition and a healthy diet, and lack of access to health services and information related to child growth and development. The purpose of this community service is to increase community knowledge in Tanjung Putra Village so that they can prevent stunting.This community service method involves active participation from the Tanjung Putra Village community through various participatory activities such as counseling about stunting, providing additional food to children aged 3-5 years, providing information about Dagusibu (get, use, save, dispose), counseling on natural ingredients that can be used as alternative medicine, and assisting the community in efforts to live a healthy life. Activities were carried out in February 2024 in Tanjung Putra Village. The results of community service showed that community knowledge about stunting and health problem management in Tanjung Putra Village increased to 80%. It is hoped that the health center will continue to provide education to the community so that it can increase public knowledge about stunting so as to prevent and solve stunting